Trust and Risk Perception in Online Marketing of Insurance ‎Products - Chaturvedi, Siddharth; Vijaykarthigeyan, Dr. K.T. (International Journal of Accounting and Economics Studies, 2025)
With the growing shift toward digitalization, the online marketing of insurance products has gained significant momentum. This study ‎explores the influence of trust and risk perception on consumer behavior in the context of online insurance marketing. Information was ‎gathered from 710 participants from different regions of India using a standard field survey between January and June 2023. The aim was ‎to measure how consumers rate trust and perceive risk factors such as data protection, information correctness, and claim validity while ‎dealing with digital insurance platforms. The research employs descriptive statistics and inferential analysis, such as multiple regression and ‎structural equation modeling (SEM), to determine the direction and strength of relationships between the most important variables. The ‎findings are that trust is central in reducing perceived risk and positively impacts willingness to buy insurance online. In addition, perceived ‎risk has a significant impact on decision-making, especially for first-time digital users and individuals who have lower digital literacy. The ‎research highlights the importance of insurance firms to increase digital transparency, have secure handling of data, and clearly communicate ‎to build customer trust and encourage broader take-up of online insurance services‎.